IMPLEMENTASI MANAJEMEN KURIKULUM PADA PROGRAM UNGGULAN NON AKADEMIK DI SDIT FIRDAUS MOJOSARI MOJOKERTO - Laili, Irfana Nurul; Hariyati, Nunuk; Roesminingsih, Erny (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aimed to know and analyze the implementation of curriculum management based on management functions: curriculum planning, curriculum organization, curriculum implementation, curriculum monitoring and evaluation, and curriculum development in the non-academic featured programs at SDIT Firdaus Mojosari. This research used qualitative research with a case study research design. This study's data collection techniques were observation, interviews, and documentation. In the data analysis technique, the researcher used condensation, data presentation, and concluding. Meanwhile, for the data validation, the researcher used the credibility of the standard of the correctness of the data and the triangulation technique. The results of the Curriculum Management research on this non-academic featured program revealed the following findings: 1) Curriculum planning for non-academic featured programs at SDIT Firdaus is prepared by involving a curriculum development team consisting of the principal, vice-principal of the curriculum, featured program coordinator, and teachers. The steps taken are analyzing the context and needs also identifying national education standards; 2) Organizing the curriculum in the featured program class by empowering the vice principal of the curriculum and the coordinator of the featured program to schedule and distribute tasks; 3) The implementation of the curriculum in the featured program class is carried out based on a predetermined schedule for the implementation of the curriculum in the featured program class; 4) Supervision and evaluation of the curriculum in the featured program class are carried out by the principal assisted by the vice-principal of the curriculum and the coordinator of the featured program. Evaluation is carried out by examining curriculum documents, interviews, and class supervision which is carried out in stages during each trimester, each semester, and at the end of the year.; 5) The curriculum development team carries out curriculum development by considering the evaluation results as a consideration in implementing curriculum development.